2005
DOI: 10.1186/1471-2091-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Nonnatural amino acid incorporation into the methionine 214 position of the metzincin Pseudomonas aeruginosa alkaline protease

Abstract: BackgroundThe alkaline protease from Pseudomonas aeruginosa (AprA) is a member of the metzincin superfamily of metalloendoproteases. A key feature of these proteases is a conserved methionine-containing 1,4-tight β turn at the base of the active site zinc binding region.ResultsTo explore the invariant methionine position in this class of protease, incorporation of a nonnatural fluorinated methionine, L-difluoromethionine (DFM), into this site was accomplished. Although overproduction of the N-terminal catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…Similar studies on MMP-2 showed unaltered activity for the serine and leucine mutants but complete loss of activity and enhanced susceptibility to proteolytic degradation for the cysteine mutant (11). In serralysins, substitution of difluoromethionine for methionine revealed no significant differences in activity or in the result of differential scanning calorimetry in Pseudomonas aeruginosa alkaline protease (12). In contrast, studies on Erwinia chrysanthemi PrtC revealed lower levels of protein expression and diminished catalytic efficiency toward resorufin-casein for the leucine (85% of the wild type), isoleucine (50%), and alanine (23%) mutants and subtle changes in the crystal structure at the active site of the first two mutants and a cysteine mutant.…”
mentioning
confidence: 63%
“…Similar studies on MMP-2 showed unaltered activity for the serine and leucine mutants but complete loss of activity and enhanced susceptibility to proteolytic degradation for the cysteine mutant (11). In serralysins, substitution of difluoromethionine for methionine revealed no significant differences in activity or in the result of differential scanning calorimetry in Pseudomonas aeruginosa alkaline protease (12). In contrast, studies on Erwinia chrysanthemi PrtC revealed lower levels of protein expression and diminished catalytic efficiency toward resorufin-casein for the leucine (85% of the wild type), isoleucine (50%), and alanine (23%) mutants and subtle changes in the crystal structure at the active site of the first two mutants and a cysteine mutant.…”
mentioning
confidence: 63%
“…However, the acylated tRNA ( 125 I-TyrtRNA CUA Gly-dCA) was prepared without any modifications to avoid the tedious procedures of isolation from the cellular mixture. Using this acylated tRNA, 125 I-Tyr-tRNA CUA Gly-dCA, the suppression efficiency was 30% [38,39]. Subsequently, they employed runoff transcription [40] to generate the semisynthetic nonsense suppressor tRNA for in vitro incorporation of L-3-[ 125 I] iodotyrosine ( 125 I-Tyr) into the 16-mer polypeptide (Met-Gly-Leu-Tyr-Leu-Gly-LeuPhe-Stop-Gly-Leu-Tyr-Leu-Gly-Leu-Phe-Stop-Stop) [41].…”
Section: Exploiting Biosynthetic Machinery: Cotranslational Approachmentioning
confidence: 99%
“…By using RSI, selenomethionine [120], difluoromethionine [125], trifluoromethionine [126], norleucine [123,127], homopropargylglycine (Hpg) [128], azidohomoalanine (Aha) [129], homoallylglycine (Hag) [130], and methoxinine [127] have been incorporated using methionyl-tRNA synthetase (MetRS); per-thiaproline, 3 [131,132]; trifluorovaline (TfV), 2-amino-3-methyl-4-pentenoic acid have been incorporated using isoleucyl-tRNA synthetase (IleRS) [133][134][135]; o-fluorophenylalanine, m-fluorophenylalanine, pFF [136], 2-pyridylalanine, 3-pyridylalanine, and 4-pyridylalanine [137] have been incorporated using PheRS; 4-aminotryptophan (4AW), 5-aminotryptophan (5AW), 4-fluorotryptophan (4FW), 6-fluorotryptophan (6FW), 5-hydroxytryptophan (5HW), 7AzW have been incorporated using TyrRS [138][139][140][141]; and trifluoroleucine has been incorporated using leucyl-tRNA synthetase (LeuRS) [142,143] in E. coli (Table 12.3). Budisa and coworkers have explored RSI for the integration of Hpg and norleucine into the superoxide dismutase (SOD) protein in yeast [123].…”
Section: Endogenous Aarsmentioning
confidence: 99%
“…Thus, it may be possible to alter the catalytic properties of these redox proteins by perturbing the electronic features of the methionine thioether group. We have previously demonstrated that the fluorinated Met analogues L-difluoromethionine (S-difluoromethyl-L-homocysteine; L-DFM) and L-trifluoromethionine (S-trifluoromethyl-L-homocysteine; L-TFM) can be biosynthetically incorporated into recombinant proteins without diminishing catalytic activity [10][11][12][13][14]. Ab initio modeling experiments with these compounds suggest that the strongly electron-withdrawing effect of the fluorine atoms on the methyl group should significantly decrease the nucleophilicity of the sulfur atom, which could alter some aspects of the interaction between this atom and a metal ligand [5].…”
Section: Introductionmentioning
confidence: 99%